Peningkatan Kualitas Sanitasi Masyarakat melalui Pembangunan Fasilitas Sanitasi di Kecamatan Tomo - Fahreza, Mohammad; Hakim, Abdul (LPPM Universitas Koperasi Indonesia, 2024)
The Community Service Program carried out in Tomo District in 2024 focuses on improving access to adequate sanitation facilities and raising community awareness about the importance of good sanitation practices. This program adopts a participatory approach, actively involving the community at every stage, from planning to evaluation. Education and training are also key components of this program, aimed at encouraging behavior change related to sanitation among the community. The program's results show a significant increase in the number of villages with access to proper sanitation facilities, from 12 villages in 2023 to 18 villages in 2024. Additionally, there was an increase in community awareness about the importance of sanitation, rising from 40% before the intervention to 75% after the intervention. This program successfully demonstrated a positive impact on public health, especially in reducing the prevalence of infectious diseases like diarrhea. This success is hoped to serve as a model for similar programs in other areas facing sanitation challenges.